1997
DOI: 10.1139/y97-154
|View full text |Cite
|
Sign up to set email alerts
|

Sequential changes of energy metabolism and mitochondrial function in myocardial infarction induced by isoproterenol in rats: a long-term and integrative study

Abstract: Acute myocardial infarction is the second cause of mortality in most countries, therefore, it is important to know the evolution and sequence of the physiological and biochemical changes involved in this pathology. This study attempts to integrate these changes and to correlate them in a long-term model (96 h) of isoproterenol-induced myocardial cell damage in the rat. We achieved an infarct-like damage in the apex region of the left ventricle, occurring 12-24 h after isoproterenol administration. The lesion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(21 citation statements)
references
References 26 publications
(21 reference statements)
3
18
0
Order By: Relevance
“…ISO, a β ‐adrenergic agonist, produces gross and microscopic infarcts in rat heart similar to those seen during myocardial ischemia in humans . Several studies have investigated the molecular and cellular mechanisms of ISO‐induced cell injury of the myocardium . We have recently demonstrated that ISO‐induced myocardial damage to rat heart in vivo involves the generation of oxidative stress .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…ISO, a β ‐adrenergic agonist, produces gross and microscopic infarcts in rat heart similar to those seen during myocardial ischemia in humans . Several studies have investigated the molecular and cellular mechanisms of ISO‐induced cell injury of the myocardium . We have recently demonstrated that ISO‐induced myocardial damage to rat heart in vivo involves the generation of oxidative stress .…”
Section: Discussionmentioning
confidence: 89%
“…Generation of oxidative stress leading to mitochondr‐ial dysfunction is one of the principal factors behind the pathophysiology of several diseases including cardiovascular disorders, Alzheimer's disease, autoimmune disorders, and cancer . Involvement of oxidative stress in the initiation and progression of ischemic heart disease has been recognized in experimental as well as in human situations . ISO, a β ‐adrenergic agonist, produces gross and microscopic infarcts in rat heart similar to those seen during myocardial ischemia in humans .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoproterenol is a synthetic β-adernoceptor agonist that its subcutaneous injection induces myocardial infarction in rats [11] and results in irreversible cellular damage and ultimately infarct-like necrosis [12,13]. The acute phase of myocardial necrosis and dysfunction induced by isoproterenol mimics changes in blood pressure, heart rate, electrocardiogram (ECG), and left ventricular dysfunction similar to that occurs in patients with myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of isoproterenol-induced myocardial injury includes cytosolic calcium overload, lipid peroxide generation and pro-coagulant activity [15,16]. The pathological process of isoproterenol-induced myocardial damage is characterized by patchy areas of myocardial ischemia.…”
Section: Introductionmentioning
confidence: 99%